2007
DOI: 10.1111/j.1095-8312.2007.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting temporal dynamics and spatial patterns of population genetic structure correlate with differences in demography and habitat between two closely-related African freshwater snails

Abstract: The relationship between habitat stability, demography, and population genetic structure was explored by comparing temporal microsatellite variability spanning a decade in two closely-related hermaphroditic freshwater snails from Cameroon, Bulinus forskalii and Bulinus camerunensis . Although both species show similar levels of preferential selfing, microsatellite analysis revealed significantly greater allelic richness and gene diversity in populations of the highly endemic B. camerunensis compared to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 89 publications
3
4
0
Order By: Relevance
“…In this study we found an excess of homozygotes and low levels of genetic diversity in all populations, which is consistent with previous studies on highly selfing freshwater snails (e.g. [ 23 , 24 , 65 67 , 69 , 70 ]). However, variable inbreeding coefficients between geographic locations have been observed in our study (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study we found an excess of homozygotes and low levels of genetic diversity in all populations, which is consistent with previous studies on highly selfing freshwater snails (e.g. [ 23 , 24 , 65 67 , 69 , 70 ]). However, variable inbreeding coefficients between geographic locations have been observed in our study (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…The genetic differentiation between the two populations from Egypt was low (0.022, not significant), and this was also true between three of the Senegalese populations (Sen_DIAM, Sen_MBO and Sen_NDO; F st 0.140–0.256, significant difference), indicating relatively high amounts of gene flow on a regional scale of 100 km (cf. Gow et al [ 23 , 24 ] in Cameroonian B. truncatus populations). In Senegal, the low differentiation might also be a relic of the Diama dam construction (see below) that was followed by a rapid expansion of snail populations, leading to highly inbred and genetically similar snail populations in the lower valley of the SRB, as was found for Biomphalaria pfeifferi in the same area [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some populations are however more closely related, and one remains somewhat apart. On the whole, all the results on population genetic structure are consistent with a system working as a metapopulation from a demographical point of view, with frequent extinction and colonization events, as observed in previous work conducted in this species (Charbonnel et al 2002a;Gow et al 2007;Campbell et al 2010;Mintsa Nguema et al 2013). However, the spatial and temporal differentiation, even if strong considering the spatial scale at which the study was conducted and affected by low effective population size, is maintained below that expected under fixation of alleles in all populations / loci by migration.…”
Section: Whitlock Andsupporting
confidence: 89%